(untitled) (Gragoatá, 2024)
This paper investigates the grammatical strategies deployed by natural languages in order to express temporal reference. We show that temporal reference is obtained by combining a finite set of pieces of meaning which are constrained by the metaphysics of natural language (BACH 1986) and which languages distribute differently across functional categories. The paper discusses more specifically temporal adverbial clauses that express the meanings of anteriority and posteriority with respect to some reference time. We consider a relevant set of languages that make use of different strategies in order to generate these meanings, and conclude that the tools that languages may deploy are of a limited number, and include tense, aspect and temporal connectives.